The Effect Of Foreign Bank Presence On Banking Competition In Asian Emerging Markets - Juwita, Tia Permata (Universitas Dehasen Bengkulu, 2025)
The consolidation process that emerged as a reaction to the 1997-1998 financial crisis led various banks to adopt international expansion strategies to broaden their operational reach. Evidence of globalization in the banking sector is the disappearance of boundaries, which allows foreign funds to flow in and out of a country easily. This study aims to examine the effect of the foreign banks presence on banking competition within that country. The presence of foreign banks is measured using a dummy variable and the percentage of foreign ownership. The research was using 543 conventional commercial banks sample in 10 Asian emerging market countries. Sampling was carried out using the purposive sampling method and hypothesis testing was performed using the Ordinary Least Squares (OLS) robust standard error method. The results show that the presence of foreign banks has a positive effect on the level of competition in the host country. The higher the level of presence and foreign ownership, the higher the level of banking competition in that country.